The Role of the Instagram Account @kompastv as a Media Supporting Democracy in Shaping the Political Awareness of Generation Z Through Discursive Analysis of User Interactions - Dien Aghni Narendraswara; Muhammad Prakoso Aji (Journal of Governance and Social Policy, 2025)
This study aims to analyze the role of the Instagram account @kompastv as a medium supporting democracy in shaping the political awareness of Generation Z through a discursive analysis of user interactions. Using a netnographic approach and critical discourse analysis, this study examines visual content such as reels, carousels, and news clips that present the chronology of political issues, direct quotes, and credible information context, thereby fulfilling the cognitive, affective, and integrative needs of young audiences according to the Uses and Gratifications theory. The results show that @kompastv functions as a digital public space that encourages discussion and the exchange of political ideas, as well as contributes to enhancing political literacy and awareness among Generation Z. Nevertheless, challenges such as misinformation and polarization are still found in user interactions. With Instagram users aged 18–34 making up 61%, this account plays a role in bridging the political information gap